2020
DOI: 10.1038/s41598-020-74463-5
|View full text |Cite
|
Sign up to set email alerts
|

KRAS K104 modification affects the KRASG12D-GEF interaction and mediates cell growth and motility

Abstract: Mutant RAS genes play an important role in regulating tumors through lysine residue 104 to impair GEF-induced nucleotide exchange, but the regulatory role of KRAS K104 modification on the KRASG12D mutant remains unclear. Therefore, we simulated the acetylation site on the KRASG12D three-dimensional protein structure, including KRASG12D, KRASG12D/K104A and KRASG12D/K104Q, and determined their trajectories and binding free energy with GEF. KRASG12D/K104Q induced structural changes in the α2- and α3-helices, prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…We substituted lysine for glutamine to mimic constitutive acetylation of K104, however, it is not entirely clear how well this mutation really phenocopies actual acetylation. For example, consistent with our prior and current work, multiple groups demonstrated that the K104Q mutation interrupts interaction with GEF leading to reduction of GEF-induced nucleotide exchange, but other study found that acetylation of K104 did not [13, 31, 32]. Our modeled structure of K-Ras with acetylated K104 suggests that acetylation of K104 should reduce GEF-induced nucleotide exchange in K-Ras.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We substituted lysine for glutamine to mimic constitutive acetylation of K104, however, it is not entirely clear how well this mutation really phenocopies actual acetylation. For example, consistent with our prior and current work, multiple groups demonstrated that the K104Q mutation interrupts interaction with GEF leading to reduction of GEF-induced nucleotide exchange, but other study found that acetylation of K104 did not [13, 31, 32]. Our modeled structure of K-Ras with acetylated K104 suggests that acetylation of K104 should reduce GEF-induced nucleotide exchange in K-Ras.…”
Section: Discussionsupporting
confidence: 89%
“…Nucleotide binding controls K-Ras functional activity by influencing its conformational state, primarily at switch I (SWI; residues [30][31][32][33][34][35][36][37][38] and switch II (SWII: residues 60-76). Although both switch regions interact with GEF, GAP, and downstream effector proteins, SWI primarily facilitates GTP hydrolysis through GAP binding and SWII plays a significant role in binding to GEF to promote nucleotide exchange.…”
Section: Introductionmentioning
confidence: 99%